Postoperative Pain and Opioid Use Following Surgical Treatment of Ankle Fractures. Issue 4 (16th October 2019) - Pate, Matthew; Hall, Jacob; Anderson, John; Bohay, Donald; Maskill, John; Padley, Michelle; Behrend, Lindsey; Yaldo, Omar
Category: Ankle, Bunion, Trauma Introduction/Purpose: Chronic opioid abuse is one of the greatest public health challenges in the United States. The most common first exposure to opioids comes from acute care prescriptions, such as those after surgery. Moreover, opioids are often prescribed excessively, with current estimates suggesting ˜75% of the pills prescribed are unused. Ankle fractures are the most common operatively treated fracture in orthopaedic surgery, and management of acute pain following surgery is challenging. The optimal perioperative pain regimen is still a point of controversy, as there is limited data available regarding appropriate amount of opioid to prescribe. This study evaluates opioid prescribing techniques of multiple foot and ankle surgeons, and associated patient outcomes. We aim to help surgeons improve their pain management practices and to limit opioid overprescription. Methods: Chart review and phone survey were performed on forty two adult patients within three to six months of ankle fracture fixation at our institution. These patients were offered to voluntarily participate in a standardized questionnaire regarding pain scores, opioid use, non-opioid analgesic use, pain management satisfaction, and patient prescription education. Results: 57% of patients reported that they were given "more" or "much more" opioid medication than needed, 38% stated that they were given the "right amount", and 5% reported that they were given "less" or "much less" than needed. 40.0% were on opioids prior to operation. 53.5% did not require refill of discharge opioid prescriptions, 30.2% of patients did not fill any posteroperative opioid prescription. 16.3% of patients filled their discharge prescription and at least one additionall refill (mean refill = 2.22). Mean number of reported opioid pills taken after surgery was 17.4. Mean satisfaction with overall pain management at phone follow up was 8.6/10. Conclusion: While postoperative pain and management vary substantially, a majority of patients feel that they are given more opioid medication than necessary following ankle fracture repair, and a majority of opioid prescriptions are not completely used. Going forward, it is likely that a majority of patients could experience the same beneficial results with less prescription opioid pain medication, which would reduce overpresciption and potential misuse.